Equity in Middle School Students’ Fractional Knowledge: Does School Type Matter in Turkey? - Aydın, Utkun; Tunç-Pekkan, Zelha; Taylan, Rukiye Didem; Birgili, Bengi; Özcan, Mustafa (OAPUB, 2017)
This study examined school type differences in fifth-grade students’ fractional knowledge with data from a university-school partnership. Students (n = 203) from a public school and a private school willing to collaborate in University within School Project participated. Results revealed that there were significant school type differences in fractional knowledge favoring private school students. Since school type differences have important impacts on the quality and equity of mathematical outcomes, we need to strongly consider the implications of these school type-related differences and pay attention particularly to the structure of schooling in public schools and the student performance in private schools.
Keywords: Middle School Students; Public Schools; Private Schools; University-School Partnership; School Type Differences